Case Report: Intact Survival of a Marginally Viable Male Infant Born Weighing 268 Grams at 24 Weeks Gestation - Arimitsu, Takeshi; Wakabayashi, Daiki; Tamaoka, Satoshi; Takahashi, Mona; Hida, Mariko; Takahashi, Takao (Frontiers in Pediatrics, 2021)
We report the case of a preterm small for gestational age male infant born at 24 weeks of gestation with a birth weight of 268 g who was discharged from our hospital without the requirement for home oxygen therapy or tube feeding. He did not experience severe intraventricular hemorrhage, periventricular leukomalacia, hearing disability, or any other serious complications. At that time (February 2019), according to the University of Iowa’s Tiniest Babies Registry, he was the tiniest male infant in the world to survive without any serious complications other than severe retinopathy of prematurity that required laser therapy. Although the survival rate of infants with extremely low birth weight is improving worldwide, a high mortality rate and incidence of severe complications remain common for infants weighing less than 300 g at birth, particularly in male infants. In recent years, there have been frequent discussions regarding the ethical and social issues involved in treating extremely preterm infants weighing less than 400 g. Despite the challenges, reports of such infants surviving are increasing. Neonatal medicine has already achieved great success in treating infants weighing 400 g or more at birth. However, lack of evidence and experience may make physicians reluctant to treat infants weighing less than this. The present case demonstrates that intact survival of a marginally viable male infant with a birth weight of less than 300 g is possible with minimal handling and family involvement beginning shortly after birth. Our detailed description of the clinical course of this case should provide invaluable information to physicians around the world who treat such infants. This report will aid in the progress of neonatal medicine and help to address many of the social and ethical issues surrounding their care.